2014
DOI: 10.24925/turjaf.v2i1.47-50.64
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of In Ovo Feeding of DL-Methionine on Hatchability and Chick Weight

Abstract: The aim of this study was to determine the effect of in ovo DL-methionine injection into the fertile broiler eggs on hatchability and relative chick weight. In the trial, 132 fertile broiler eggs were obtained from a breeder flock (34-wk-old Ross 308 parent stock). Fertile eggs were randomly assigned to two experimental groups. Experimental groups were 1) Control 2) DL-methionine injected group with three replicates. Injections were carried out at the 16th day of incubation. At the end of the study, hatchabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
2
12
2
Order By: Relevance
“…Similar findings were recorded by Foye et al, (2006) who found that in ovo injection of egg white protein and, HMB, carbohydrate increased hatch weight in broiler chicks. Similar results of improved hatch weight in broilers were reported by Isa Coskun et al, (2014).…”
Section: Resultssupporting
confidence: 89%
“…Similar findings were recorded by Foye et al, (2006) who found that in ovo injection of egg white protein and, HMB, carbohydrate increased hatch weight in broiler chicks. Similar results of improved hatch weight in broilers were reported by Isa Coskun et al, (2014).…”
Section: Resultssupporting
confidence: 89%
“…This is in agreement with previous studies in that IOF of dextrin, l ‐arginine, vitamin C and grape seed extract improved hatchability. However, other results showed that IOF decreased or did not affect the hatchability. These variable results may be ascribed to different nutrients and injection techniques among studies.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, there are reports pointing out the reduced hatchability by Thr in ovo administration (Salmanzadeh et al., ). Generally, hatchability is affected by in ovo injecting site and time (Ohta and Kidd, ), depth of injection (Coşkun et al., ) and also type of injecting substance. As such, a possible explanation for contradictory results in the case of hatchability might be due to the combination of technical procedure and substance that used for in ovo injection.…”
Section: Discussionmentioning
confidence: 99%